Hear The Unheard: A Qualitative Research of Adolescent Life Meanings After Experiencing Parental Abuse - Kresna Hadi Soetjipto; Salsabila Ayu Fida Pusparini; Latipun Latipun (Riviera Publishing, 2024)
Violence experienced by adolescents has an impact on them both in terms of personality and the way they view life. This study aims to find out how the lives of adolescents who experience family violence become meaningful. The research method in the study used a qualitative approach with a phenomenological research type. Participants were selected using a purposive sampling system with data collection methods in the form of in-depth interviews with five participants. The results showed that adolescents who were victims of violence by their parents interpreted life in various ways. They lose trust in others and see life as a struggle for survival. They no longer identify their parents as parental figures. Teenagers see parents as threatening and insecure. Adolescent victims of violence fill their lives with sadness because they do not get affection, and they want freedom from their parents. This study concludes that adolescents who experience violence tend to try hard to survive the hard life they get. The findings of this study underscore the profound impact of family violence on adolescents' perceptions of their lives and interpersonal relationships. Understanding these experiences is critical to developing targeted interventions and support systems aimed at reducing the long-term effects of violence.